2019
DOI: 10.1002/hed.25552
|View full text |Cite
|
Sign up to set email alerts
|

Classification of tumors by imaging diagnosis and preoperative fine‐needle aspiration cytology in 120 patients with tumors in the parapharyngeal space

Abstract: Background Tumors in the parapharyngeal space are rare, and preoperative diagnosis is difficult because of anatomical and histological complexity. Methods To evaluate the usefulness of preoperative diagnosis, we compared the classification of tumor localization in the prestyloid and retrostyloid compartments by imaging and preoperative cytological diagnosis by fine‐needle aspiration cytology with the postoperative histopathological diagnosis in 120 patients with tumors in the parapharyngeal space. Results Tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…All four preoperative fine-needle aspiration biopsies were inconclusive by Luna-Ortiz et al , but a study by Matsuki et al showed 95.2% diagnostic rate of FNAC in PPS tumors, however among those neurogenic tumors of retrostyloid compartment had high diagnostic rate (33%)of inadequate samples. [ 13 18 ] The pathological finding is suggestive of hybrid PNST with mixed features of schwannoma and neurofibroma. IHC stain profile is consistent with the diagnosis of hybrid neurofibroma/schwannoma, S100 and GFAP positivity confirms a neural tumor and negative SMA excludes muscular tumor.…”
Section: Discussionmentioning
confidence: 99%
“…All four preoperative fine-needle aspiration biopsies were inconclusive by Luna-Ortiz et al , but a study by Matsuki et al showed 95.2% diagnostic rate of FNAC in PPS tumors, however among those neurogenic tumors of retrostyloid compartment had high diagnostic rate (33%)of inadequate samples. [ 13 18 ] The pathological finding is suggestive of hybrid PNST with mixed features of schwannoma and neurofibroma. IHC stain profile is consistent with the diagnosis of hybrid neurofibroma/schwannoma, S100 and GFAP positivity confirms a neural tumor and negative SMA excludes muscular tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding correlation with definitive histopathology, FNAC properly diagnosed most pleomorphic adenomas, but was not more informative in the remaining cases. Given the substantial histological heterogeneity of salivary gland tumors, determining the exact subtype of tumor based only on FNAC is a well-known challenge [ 18 , 26 , 27 ]. Transoral biopsies should be performed only in cases where transoral resection is feasible and intended, because it may complicate later transcervico-parotid tumor removal and be associated with tumor spillage.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant tumors account for 12.7%-20%. 3,4 Their proximity to important nerves and blood vessels, such as the lower cranial nerves and internal carotid artery, restricts the surgical field, making surgery difficult and prone to postoperative complications. 5 Oncocytoma is a rare benign epithelial tumor that occurs in the salivary glands, kidneys, and thyroid gland.…”
Section: Introductionmentioning
confidence: 99%